Predictors of low cardiac output syndrome after combined mitral and tricuspid valve surgery - Labaste, François; Lavie-Badie, Yoan; Bouchau, Robin; Boyère, Lucie; Sanchez-Verlaan, Pascale; Gonzalez, Hélène; Marcheix, Bertrand; Botea, Roxana; Vardon-Bounes, Fanny; Minville, Vincent (Frontiers in Cardiovascular Medicine, 2024)
Introduction Low cardiac output syndrome (LCOS) is a common complication in cardiac surgery, and we evaluated the incidence of its early occurrence after mitral and tricuspid combined cardiac surgery and its associated risk factors. Material and method Retrospective, single institution study. We included 88 consecutive adult patients with severe mitral insufficiency scheduled for elective mitral and tricuspid valve replacement surgery between January 2015 and November 2018. The primary endpoint was the occurrence of LCOS, defined as the need for inotropic support or circulatory assistance after surgery. The secondary endpoint was mortality at 30 days. Results LCOS occurred in 26 patients (29.5%) of the studied patients and its associated risk factors that appeared in the multivariate analysis were chronic kidney failure [adjusted odds ratio (OR) 3.1; 95% confidence interval (CI) 1.0–9.9, p = 0.05], pre-operative left ventricular heart failure (OR 5.3; 95% CI 1.3–10.9, p = 0.002), pre-operative right ventricular heart failure (OR 3.6; 95% CI 1.1–11.5, p = 0.02), and mitral valve replacement (OR 3.9; 95% CI 1.2–12.6, p = 0.03). LCOS affected the survival of patients (HR = 5.5; 95% CI 1.1–27.7 p = 0.04). Conclusion LCOS is a frequent complication after mitral and tricuspid combined surgery and is associated with poor prognosis.